Biological Control of Mosquitoes Cluex pipiens Using Locally Isolate of Bacillus Thuringiensis in Diyala Province - Sarmad Qassim Mohammad (Journal of Global Pharma Technology, 2016)
The study included isolating, diagnosing and studying the ability of  Bacillus thuringiensis to kill Culex pipiens larvae, the samples were isolated from different places of agricultural soils in Diyala province. The results of the fermentation medium to grow the B thuringiensis inoculums showed that the best liquid fermentation medium was the barley extract, with 20 gm. A ratio of sucrose per liter mixed with 20 mg of the Amoxicillin antibiotic. The bacterial density in it was 221x106 colony forming unit/ml. Then carry the bacterial suspension on calcium carbonate, preparation three concentrations (1, 2, 3g) of the dry preparation/liter of sterilized water. The results show that the effect of different concentrations of B.thuringiensis on the death rate larvae of Culex pipiens was significant, it was the highest value of dead larvae it was (2.52) at 3 g/L concentrations of B. thuringiensis sand the lowest value of dead larvae it was (0.92) at 1 g/L concentration of B.thuringiensis, at a significant level (0.05).  There were also significant differences between the days, the highest value of dead larvae it was in the fourth day of treatment (2.55) and the lowest value of dead larvae it was on the first day of treatment (0.15) at a significant level (0.05). Twenty-four hours after the initiation of the treatment of larvae Culex pipiens with the bio product of B.thuringiensis, she appeared symptoms of change in behavior, slowed the moving of larvae gradually until completely stopped movement and shrunk, due to the effect of crystalline protein , which decomposes in the middle gut of the larvae and is associated with receptors in the membrane of the gastrointestinal tract, then poison enters the membrane causing the weakness of the epithelial cells and swelling and dissolution causing holes in the membrane  or that the toxins of the bacteria may lead to a disturbance in the nervous system leading to paralysis in the organs responsible for feeding and then the death of larvae from hunger.Keywords: Bacillus thuringiensis, Bioproduct, Mosquitoes, Culex pipiens, Larvae, death.